Applying Nida’s Scientific Approach and Chomsky’s TG Grammar to Recent English Translations of Iqbal’s Shikwa and Jawab-e-Shikwa - Huma Imran; Alina Nisar; Maryum Hanif (Journal of Religion and Society, 2025)
This research focuses on analyzing the convert of Allama Iqbal’s Urdu poems: Shikwa (The Complaint) and Jawab-e-Shikwa (The Response to the Complaint) in the English language with special reference to the linguistic and cultural translation. Because of their themes and style, these poems pose several translation difficulties. To implement features of syntactic and semantic transformations during translation the Scientific Approach is applied along with the use of Eugene Nida’s dynamic and formal equivalence and Noam Chomsky’s Transformational-Generative (TG) Grammar. As a result of comparing the translation made by Sultan Zahoor Akhtar and Altaf Hussain this research investigates how the interpreter solves the conflict between a close translation to the source text and the understanding of the text in English language. As findings are disclosed, it is more problematic to argue that animals do not restructure sentences in the same way; that they are either more or less semantically precise; or that they do not associate certain images as specific cultures do. Keywords: Translation Studies, Dynamic Equivalence, Formal Equivalence, T-G Grammar, Syntactic transformations, Semantic Precision